A general number-to-space mapping deficit in developmental dyscalculia. (August 2015) - Huber, S.; Sury, D.; Moeller, K.; Rubinsten, O.; Nuerk, H.-C.
Highlights: A general mapping deficit of DD in number line estimation was investigated. The performance in a newly developed number line learning task was assessed. Adults with DD performed worse for any (non-)linear number-to-space mapping. Adults with DD compensated for the impairment by relying on reference points. This indicates a general impairment of mapping symbolic numbers onto space. Abstract: Previous research on developmental dyscalculia (DD) suggested that deficits in the number line estimation task are related to a failure to represent number magnitude linearly. This conclusion was derived from the observation of logarithmically shaped estimation patterns. However, recent research questioned this idea of an isomorphic relationship between estimation patterns and number magnitude representation. In the present study, we evaluated an alternative hypothesis: impairments in the number line estimation task are due to a general deficit in mapping numbers onto space. Adults with DD and a matched control group had to learn linear and non-linear layouts of the number line via feedback. Afterwards, we assessed their performance how well they learnt the new number-space mappings. We found irrespective of the layouts worse performance of adults with DD. Additionally, in case of the linear layout, we observed that their performance did not differ from controls near reference points, but that differences between groups increased as the distance to reference point increased. We conclude that worse performance of adults with DD in the number line task might be due a deficit in mapping numbers onto space which can be partly overcome relying on reference points.